Investigations of arsenic substitution on the physical, electrical and magnetic properties of Bi-2212 superconductors. (1st November 2020) - Labban, W.; Malaeb, W.; Habanjar, K.; Hassan, M.S.; Sakagami, R.; Kamihara, Y.; Awad, R.
ABSTRACT: The effect of Arsenic substitution on the properties of Bi-2212 superconductors was studied. Solid-state reaction technique was used for the synthesis of Bi2−x Asx Sr2 Ca1.1 Cu2.1 O8 samples, x = 0, 0.1, 0.2 and 0.4. The X-ray diffraction confirmed the formation of the tetragonal phase of Bi-2212 superconductors. The decrement in the c parameter confirmed that As insertions were introduced into the Bi sites of the system. The grain morphology of the surface was analysed by scanning electron microscopy, where the amount of arsenic increases with As substitution. The superconducting transition temperature (Tc ) was determined from the DC-electrical resistivity by the standard four-probe technique. Tc was enhanced up to x = 0.1 above which it was suppressed. For magnetism, half magnetic-hysteresis loops were obtained by SQUID magnetometer at different temperatures (5 and 30 K). The hysteresis loops sizes increased with increasing As-concentrations. The critical current density (Jc ) and the flux pinning mechanisms were investigated via different models.